The Community Views on the Role of Komunitas Permainan dan Olahraga Tradisional Indonesia (KPOTI) (Media Ilmu Keolahragaan Indonesia, 2022)
The Folk games can develop well and go according to plan through the right container and place. These people's games can be of quality and have value for the community through organizations and communities in the area. The aim of this study was to find out the Community's View of the Role of the Committee for Folk Games and Traditional Sports (KPOTI) in Semarang Regency. This research was conducted at Bung Karno Square, Semarang Regency in May. The method used in this study was a survey, data collection was carried out using non-probability sampling. The technique for collecting data in this research was to provide an instrument in the form of a questionnaire to the respondents to find out the views of the community on the role of the Committee for Folk Games and Traditional Sports (KPOTI) in Semarang Regency. This study gave the result that the Community's View of the Role of the Committee for Folk Games and Traditional Sports (KPOTI) of Semarang Regency with a total of 80 respondents. This study responded to the results in the field with a view of resources in the good category as many as 65 people (60%), medium as many as 10 people (37%) and low as many as 5 people (3%). From the point of view of infrastructure, there are 20 people (30%) in the good category, while there are 58 people (67%) and 2 people (3%) in the low category. From the point of view of organizational management, there are 40 people (60%) in the good category, while there are 30 people (35%) and 10 people (5%) in the low category. Thus, the overall data obtained results in a good category of 67 people (72%), a moderate category of 10 people (26%) and a low category of 3 people (2%).